Pelatihan Pengembangan Modul Ajar Biologi Bermuatan Kearifan Lokal bagi Guru di Cikalong Wetan, Kabupaten Bandung Barat - Bambang Supriatno; Tri Suwandi; Saefudin Saefudin; Kusnadi Kusnadi; Zuliande Zidan (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2023)
The potential for local wisdom of an area to be utilized to construct learning to be more contextual. However, for some teachers, integrating local wisdom in learning, especially in biology teaching modules, is a challenge. Therefore, a community service program (PkM) was implemented to improve teachers' abilities in developing biology teaching modules containing local wisdom. This program was implemented in a hybrid manner, namely a face-to-face workshop in Cikalong Wetan District on 12 August 2023 and continued online for assistance in preparing teaching modules on 13-19 August 2023. A total of 28 Science/Biology teachers were involved in this program and were divided into three groups. teaching module developer. The stages undertaken by participants in developing the teaching module are: (1) identifying the potential of local wisdom in Cikalong Wetan, (2) analyzing the relationship between local wisdom and biological content, science process skills, and value content, (3) creating an outline of the teaching module, (4) developing teaching module content, (5) reviewing teaching modules, and (6) revising teaching modules. A total of three teaching modules were successfully prepared, namely with the themes of angklung, peuyeum, and water source conservation. Based on the results of n-gain data analysis, it was found that teachers' knowledge about developing teaching modules containing local wisdom increased to the "sufficient" category. Apart from that, based on the results of the questionnaire, it is known that the majority of participants responded well to this program.